A Real-Time Sign Language Prediction Framework Enhancing Eommunication for Specially Abled People - Jeya Ganesan, J; Sathiya, A; Vedhagiri, A; Radha Rukman, B (2024 International Conference on Communication, Computing and Internet of Things (IC3IoT), 2024)
Technology has advanced significantly. By recording and analyzing speech against existing data, we can interpret communication from mute or deaf individuals. Our proposal introduces technology to aid people with disabilities like Deafness, Mutism, or Blindness, acting as sensory substitutes. Object recognition through image processing grants the blind vision, while Bluetooth or radio-enabled text-to-speech and speech-to-text features facilitate communication for the deaf and mute.